The Impact of Terrorism on Tourism Destination Image and Development - Khan, MD Yusuf Hossein; Mendes, Julio Da Costa (Asian Administration and Management Review, 2019)
In the twenty first century, tourism is emphasized from multidimensional factors that have been ever. Starting from top of the government body to the private business sectors, tourism has tiled away path for discovering new opportunities for many countries that were untapped unstill very recently. While the world yet thinks natural resources like oil, gas, gold and other mines to be the most valuable resources that determined the destiny of a particular country or state, tourism now steps up and shows the potential to that race of greatness. However, tourism is now rather an industry encompassing various kinds of business ventures entitled to the people’s traveling. From the hotel and restaurant business to travel companies, many other parties are now involved within this industry. This research paper investigated the impact of terrorism on international tourism to see whether it affects the global tourism negatively. For the analysis, the researchers designed the research methodologies that are attributed to facilitate the research conduction process. For this, a deductive research approach followed by positivism research philosophy has been followed. The researchers designed a set of questionnaire contained 10 close ended questions in survey monkey. Around 100 respondents gave their opinion on the global terrorism and tourism issues where it has been found that they are more concerned about the security and safety. Hence, most of the visitors sharply avoid places that are highly exposed to terrorist attacks. As recently the developed countries like France, USA and UK are facing an extreme rivalry and threats against terrorism; there has been a significant fall in the revenue while developing countries are having fewer problems with global terrorism issues. The detail outcomes are given in the result analysis part. Finally, for better future effectiveness, some recommendations are provided.